Inside the meltdown [videorecording (DVD)] - Kirk, Michael; Gilmore, Jim; Lyman, Will, 1948- (PBS Video, 2009)
Frontline investigates the causes of the worst economic crisis in 70 years and how the government responded. The film chronicles the inside stories of the Bear Stearns deal, Lehman Brothers collapse, the propping up of insurance giant AIG and the $700 billion bailout.